2020
DOI: 10.30773/pi.2020.0045
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Temporal Activation During a Verbal Fluency Task is Associated with Poor Motor Speed in Patients with Major Depressive Disorder

Abstract: Objective Substantial research has revealed cognitive function impairments in patients with major depressive disorder (MDD). However, the relationship between MDD cognitive function impairment and brain activity is yet to be elucidated. This study aimed to reveal this relationship using near-infrared spectroscopy (NIRS) to extensively measure frontotemporal cortex function.Methods We recruited 18 inpatients with MDD and 22 healthy controls. Regional oxygenated hemoglobin changes (oxy-Hb) were measured during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…The study results led us to conclude that the reduced brain activation in the frontal-temporal lobe during VFT in patients with MDD compared with the HCs indicated decreased frontal–temporal lobe function in depressed patients. The result is consistent with previous studies ( 41 , 42 ) may be a neuropathological basis for cognitive dysfunction in depressed patients. We also found that activation was lower in the right side of the brain in the MDD group, which was in line with prior studies ( 13 , 43 ).…”
Section: Discussionsupporting
confidence: 93%
“…The study results led us to conclude that the reduced brain activation in the frontal-temporal lobe during VFT in patients with MDD compared with the HCs indicated decreased frontal–temporal lobe function in depressed patients. The result is consistent with previous studies ( 41 , 42 ) may be a neuropathological basis for cognitive dysfunction in depressed patients. We also found that activation was lower in the right side of the brain in the MDD group, which was in line with prior studies ( 13 , 43 ).…”
Section: Discussionsupporting
confidence: 93%
“…Zhang et al (2020) found that significant alterations of brain synchronization occurred in frontal, temporal, parietal-occipital regions of left brain and temporal region of right brain in MDD patients. Another studies (Li et al, 2017;Kiriyama et al, 2020) found that the left temporal region plays a critical role in MDD patients. Combined with our findings, the frontal and left temporal lobes may play an important role in the pathogenesis of MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas most research showed bilateral prefrontal significantly lower activation. [17][18][19] In addition, recent study suggest remitted depressive patient showed left frontotemporal lower hemodynamic activations. 20 One major reason that may explain the inconsistency is that samples contains clinical subtypes such as refractory depression.…”
Section: Introductionmentioning
confidence: 96%